A mobile knowledge management system architecture in higher education institution - Chuan, Butt Chin; Alias, Rose Alinda (2004)
This paper proposes systems architecture for a mobile knowledge management system (KMS).The architecture is based on a review of system architectures of several mobile-based applications. The architecture is designed to be appropriate to the context of an IHL.